Effects of the association of physical exercises and self-drainage in the treatment of cellulite - Anna Balsamo; Francesca Panero; Eneida de Morais Carreiro; Riccardo Castellini; Martina Castellino; Ana Laura Martins de Andrade; Patrícia Froes Meyer (Physiotherapy Quarterly)
Introduction Cellulite is a descriptive term used to characterise the topographic alteration of the skin, with a high prevalence in females. Manual lymphatic drainage (MLD) stands out as a technique that, when used alone or associated with other techniques such as exercises and/or physical activities, improves the general appearance of this condition. To evaluate the effects of self-MLD associated with supervised kinetic exercises in the treatment of cellulite and improvement in the quality of life of patients.